1986
DOI: 10.3181/00379727-182-42349
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age and Genotype and Circulating Concentrations of Triiodothyronine (T3), Thyroxine (T4), and Growth Hormone in Commercial Meat Strain Chickens

Abstract: The presence of the sex-linked dwarf gene (dw) in homozygous male (dwldw) and female (dw/-) meat strain chickens is associated with a significant reduction in circulating levels of triiodothyronine (T3). Heterozygous (Dw/dw) male broiler strain chickens have T3 concentrations similar to those in homozygous (Dw/Dw) male broilers. Genetically normal (Dw/Dw) but significantly slower growing roaster strain male meat chickens had consistently higher T3 than the faster growing broilers at all ages in one experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Across all four treatments, chicks that gained the most weight from 21 to 28 days had significantly lower GH concentrations, and this was independent of differences in feed consumed during this time. These data support the hypothesis of Lilburn et al (1986a) that measured differences in GH are effected by rates of gain during some arbitrary time period, and that genetic potential and diet influence GH through their influence of growth rather than having direct effects per se. Fox et al (1972;1974) reported similar findings with beef steers.…”
Section: Ab Bsupporting
confidence: 75%
See 2 more Smart Citations
“…Across all four treatments, chicks that gained the most weight from 21 to 28 days had significantly lower GH concentrations, and this was independent of differences in feed consumed during this time. These data support the hypothesis of Lilburn et al (1986a) that measured differences in GH are effected by rates of gain during some arbitrary time period, and that genetic potential and diet influence GH through their influence of growth rather than having direct effects per se. Fox et al (1972;1974) reported similar findings with beef steers.…”
Section: Ab Bsupporting
confidence: 75%
“…Any dietary or genetic factors that decrease BW gain generally will result in increased circulating growth hormone (GH) (Marks, 1979;Burke and Marks, 1982;Lilburn et al, 1986a;Lauterio and Scanes, 1987). The data herein suggest that during a period of nutritional rehabilitation, GH concentrations may be influenced more by absolute weight gain during the repletion period rather than by starting BW or feed intake during the period.…”
Section: Ab Bmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been reported that plasma concentrations of GH decline with age earlier in broiler than layer breeds (Scanes and Harvey, 1982). The observed progressive sexual dimorphism in somatotroph numbers may contribute to higher circulating GH concentrations in male vs. female broiler or meat-strain chickens, as reported in other studies (Burke and Marks, 1982;Stewart and Washburn, 1983;Lilburn et al, 1986).…”
Section: Age (Weeks)mentioning
confidence: 66%
“…genotype X environment interactions) and to improve selection methods. Although it is clear that pituitary and thyroid hormones can play an important role in these processes (Scanes et al, 1984(Scanes et al, , 1986Lilburn et al, 1986;Decuypere and Kiihn, 1988) no complete picture of the relationships between these hormones and protein gain and efficiency is available.…”
Section: Introductionmentioning
confidence: 98%